Cognitive Distortions and Decision-Making in Women Victims of Intimate Partner Violence: A Scoping Review - Marta Badenes-Sastre; Patricia Medinilla-Tena; Chelsea M. Spencer; Francisca Expósito (Psychosocial Intervention)

(untitled)
Objective: Exposing women to intimate partner violence (IPV) poses a risk to their physical and mental health, necessitating that they leave the relationship. However, women face various obstacles in doing so, such as cognitive distortions that affect their interpretation of the reality of violence, trapping them and significantly influencing their decision to leave. This scoping review explores, synthesizes, and analyzes the available evidence on the relationship between cognitive distortions and decision-making among women involved in IPV. Method: A systematic search was performed following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews guidelines, utilizing the Web of Science, Scopus, and ProQuest databases. A total of 12 studies (five qualitative, four quantitative, and three mixed methodology) were included according to the inclusion criteria. Results: Self-blame, low attribution of responsibility to the aggressor, minimization of violence or damage, normalization of IPV, denial/loss of self, denial injury, control perceived, hope of change, savior beliefs, “should” belief in the relationship, focus on positive aspects of the relationship or aggressor, and denial other emotional options besides the partner were the main cognitive distortions found in women victims of IPV and related to maintaining IPV. Conclusions: These findings highlight the importance of recognizing and addressing cognitive distortions in women, which is crucial in preventing them from becoming trapped in violent relationships. Future research should continue to investigate the role of cognitive distortions in women’s decision-making regarding IPV, as well as the consequences of leaving the aggressor for them.